1993
DOI: 10.1055/s-2006-959758
|View full text |Cite
|
Sign up to set email alerts
|

Five New Prenylatedp-Hydroxybenzoic Acid Derivatives with Antimicrobial and Molluscicidal Activity fromPiper aduncumLeaves

Abstract: Five new prenylated benzoic acid derivatives, methyl 3-(3,7-dimethyl-2,6-octadienyl)-4-methoxybenzoate (1), 1-(1-methylethyl)-4-methyl-3-cyclohexenyl 3,5-bis(3-methyl-2-butenyl)-4-hydroxybenzoate (2), 1-(1-methylethyl)-4-methyl-3-cyclohexenyl 3,5-bis(3-methyl-2-butenyl)-4-methoxybenzoate (3), methyl 3,5-bis(3-methyl-2-butenyl)-4-methoxybenzoate (4), and 4-hydroxy-3-(3-methyl-2-butenyl)-5-(3-methyl-2-butenyl)-benzoic acid (5) were isolated from the dried leaves of Piper aduncum L. (Piperaceae). Together with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 8 publications
5
66
0
5
Order By: Relevance
“…Phytochemical studies of the compositions of these two species of Piper from PNG have been reported [10,[13][14][15][16][17]. Four new cytotoxic alkenylphenol compounds, designated gibbilimbols A-D were obtained from P. gibbilimbum and their chemical structures established from spectroscopic evidence [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemical studies of the compositions of these two species of Piper from PNG have been reported [10,[13][14][15][16][17]. Four new cytotoxic alkenylphenol compounds, designated gibbilimbols A-D were obtained from P. gibbilimbum and their chemical structures established from spectroscopic evidence [10].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical investigation of P. aduncum revealed a new amide, designated as aduncamide [13], three new dihydrochalcones, designated as piperaduncins A -C [14], five new prenylated p-hydroxybenzoic acid derivatives [15], five new unusual monoterpene substituted dihydrochalcones, designated adunctins A -E [16], three new natural products derivatives of chromene and benzoic acids [17] as well as other known chemical compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Both compounds had been previously isolated from P. aduncum. [9][10][11][12] Dillapiol. 1 (27), 133 (29), 105 (40).…”
Section: Identification Of the Marker Compoundsmentioning
confidence: 99%
“…P. aduncum was registered in the First Edition of Brazilian Pharmacopeia 8 and many studies in the literature describe its phytochemicals and its antimicrobial effects. 9,10 This work describes part of the efforts for the standardization and quality control of hydroalcohol extracts of P. aduncum, based on the HPLC quantification of some marker compounds. This was a colaborative work with Siema Eco Essências da Amazônia, a company that develops an antimicotic product trademarked as Dermodilapiol from aerial parts of Piper aduncum.…”
mentioning
confidence: 99%
“…3 Piper aduncum L., known as fake jaborandi , is reported in folk medicine as diuretic, wound healing and antihemorrhagic, 4 Piper regnellii (Micah) C. DC has antifungal activity 5 and Piper hispidinervum C. DC. is used in the manufacture of fixative for fragrances and as natural insecticides.…”
Section: Introductionmentioning
confidence: 99%